Legal Problems of Protecting Personal Data of Citizens in the Republic of Kazakhstan - Tilep, T.S.; Juchnevicius, E. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The article examines the current state of legislation governing the protection of personal data, the challenges arising in its implementation, and the prospects for improving the protection mechanism through the use of blockchain technology. Frequent cases of unlawful dissemination of personal data in Kazakhstan are directly linked to unresolved issue of cybersecurity and the need to address vulnerabilities in the existing legislation, which underscores the relevance of the chosen research topic. The purpose of this study is to establish a legal framework for the protection and security of personal data through the use of digital technologies. The scientific novelty of this work lies in the fact that, for the first time since the formation of the legislative framework governing personal data in the Republic of Kazakhstan, legal norms regarding personal data have been defined, as well as areas of legal regulation for the circulation of certain types of personal data. Measures to improve existing legislation governing the circulation of personal data have been proposed. The above constitutes a national scientific doctrine in the field of personal data protection. New practical conclusions have been summarized, allowing for the improvement of existing national legislation and, consequently, their application in legislative activity. The research methods used include a general logical approach (induction, deduction), systematization, analysis, formulation, scientific methods, and empirical methods. Ensuring the security of personal data is a state obligation arising from the duty to protect individual human rights; therefore, the authors emphasize the particular importance of strengthening control over digital threats and introducing a procedure for assessing their impact on human rights in accordance with international standards. The study concludes that the Republic of Kazakhstan should accede to international instruments establishing standards for the protection of personal data. A potential pathway for strengthening the legal framework on personal data protection lies in establishing systemic safeguards that restrict unauthorized access to information. Such mechanisms should operate across all levels of data governance, ensuring consistent compliance among data holders, processors and supervisory entities. Based on the results of the research, it is proposed to adopt a legal norm regulating continuous control and monitoring by data owners, operators, and persons responsible for organizing the processing and storage of personal data.